Workshop on the Deep Continental Crust of South India - Ashwal, Lewis D.; orcid:0000-0001-7277-9007 (Lunar and Planetary Institute, 1988)
The various theories in the field on the Southern Indian granulite formation are discussed. Some widely accepted ideas about the origin of granulites, particularly relating to the role of metamorphic fluids, will have to be modified. Extended abstracts of the papers presented, summaries of the attendant discussions, up-to-date accounts of the geology of the South Indian Precambrian Shield, and detailed field trip guides are presented. sponsored by Geological Society of India . [and others] edited by Lewis D. Ashwal convened by Lewis D. Ashwal . [and others] sponsored by Geological Society of India . [and others] hosted by Institution of Engineers, Bangalore, Department of Geology, University of Mysore [and] Centre for Earth Science Studies, Trivandrum, January 9-23, 1988. Gneiss-Charnockite-Granite Connection in the Archaean Crust of Karnataka Craton, India / Iyer, G.V. Anantha -- Geochemistry of Amphibolites from the Kolar Schist Belt / Balakrishnan, S.; Hanson, G.N.; Rajamani, V. -- Nature of the Coast Batholith, Southeastern Alaska: Are There Archean Analogs? / Barker, F.; Arth, J.G. -- Water Activities in the Kerala Khondalite Belt / Chacko, T. . [and others] -- Significance of the Late Archaean Granulite Facies Terrain Boundaries Southern West Greenland / Friend, C.R.L.; Nutman, A.P.; McGregor, V.R